2012
DOI: 10.3791/3466
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microregional Hypoxia in Mouse Cerebral Cortex by Two-photon Imaging of Endogenous NADH Fluorescence

Abstract: The brain's ability to function at high levels of metabolic demand depends on continuous oxygen supply through blood flow and tissue oxygen diffusion. Here we present a visualized experimental and methodological protocol to directly visualize microregional tissue hypoxia and to infer perivascular oxygen gradients in the mouse cortex. It is based on the non-linear relationship between nicotinamide adenine dinucleotide (NADH) endogenous fluorescence intensity and oxygen partial pressure in the tissue, where obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
4
0
4
Order By: Relevance
“…Previous studies have shown that hypoxia can enhance NAD(P)H levels. 36,37 Here, we investigated the imaging ability of TCF-MQ for NAD(P)H in HepG2 cells under hypoxia (1% O 2 ) and normoxia (20% O 2 ), respectively. HepG2 cells were cultured under hypoxic or normoxic conditions for 12 h, and then incubated with 10 mM TCF-MQ for 5-25 min.…”
Section: Bioimaging Of Nad(p)h In Living Cellsmentioning
confidence: 99%
“…Previous studies have shown that hypoxia can enhance NAD(P)H levels. 36,37 Here, we investigated the imaging ability of TCF-MQ for NAD(P)H in HepG2 cells under hypoxia (1% O 2 ) and normoxia (20% O 2 ), respectively. HepG2 cells were cultured under hypoxic or normoxic conditions for 12 h, and then incubated with 10 mM TCF-MQ for 5-25 min.…”
Section: Bioimaging Of Nad(p)h In Living Cellsmentioning
confidence: 99%
“…Tubular epithelial cell swelling causing a reduction in interstitial space was observed during ischaemia. Cell swelling is a common observation during hypoxic conditions within many cell types (Heiss, 2012), and in tubular epithelial cells of the renal cortex is due to osmotic dysregulation by disturbed sodium potassium (Na + /K + ) ATPase function (Molitoris et al, 1992;Coux et al, 2009) with intravital MPM results from rats with AKI after IR injury , and similar findings have been demonstrated in brain with microregional hypoxia (Polesskaya et al, 2012) and in assays of NADH in isolated renal tubule preparations after various short-chain fatty acid, carboxylic acid, and amino acid treatments (Balaban and Mandel, 1988). Interestingly, early studies investigating renal IR-induced injury have demonstrated that the occlusion of small vessels caused by tubular swelling can contribute to the pathology of ensuing reperfusion injury (Obermuller et al, 1997).…”
Section: Discussionmentioning
confidence: 66%
“…A forte correlação das alterações microcirculatórias com a PAM indicaram que, apesar dos mecanismos compensatórios serem capazes de preservar a microcirculação cerebral inicialmente durante a hemorragia, essa resposta provavelmente estaria restrita aos limites de pressão de autorregulação cerebral (Werner et al, 2005), assim como observado para a PPC no modelo porcino. A densidade numérica dos capilares cerebrais está altamente correlacionada à densidade e metabolismo neuronal, dada sua alta demanda metabólica (Kasischke et al, 2011;Polesskaya et al, 2012). Isso sugere que a notável redução no número e área de superfície de capilares perfundidos no cérebro teve um grande impacto sobre a ocorrência de disfunção mitocondrial e eletrocortical após a hipotensão hemorrágica, corroborando com a forte correlação positiva entre estas três variáveis no presente estudo.…”
Section: Todos Os Tratamentos Reverteram Os Baixos Níveis De Oxigêniounclassified
“…Este resultado foi semelhante ao obtido pela indução e reversão da hipóxia, respectivamente, através da manipulação da fração inspirada de oxigênio, mesmo sem comprometimento cardiovascular (Nair et al, 1975;Kasischke et al, 2011;Polesskaya et al, 2012). Estes resultados demonstraram a imediata responsividade da função mitocondrial frente às manipulações de oxigênio, confirmando a recuperação da oxigenação pela restauração do suprimento sanguíneo nos grupos tratados com terlipressina.…”
Section: Todos Os Tratamentos Reverteram Os Baixos Níveis De Oxigêniounclassified
See 1 more Smart Citation